Colina e metionina+cistina digestível para codornas em fase de postura - Griep Júnior, Dirceu Neutzling (2017)
The objective of this study was to evaluate the ratio between choline and digestible methionine + cystine in laying quail diets on performance characteristics, egg quality and nitrogen excretion (N). The experiment was carried on in a 4x2 factorial scheme, considering four levels of choline (0.0, 0.042, 0.084 and 0.126%) and two levels of digestible methionine (0.857% and 0.685%), totaling eight treatments, five replications and seven birds in each plot, distributed in a completely randomized design. The parameters evaluated were: feed intake, percentage of laying, feed conversion (FC) per dozen and mass of eggs, egg weight, Haugh unit, bark thickness, specific gravity, percentage of bark, yolk and albumen percentage and excreted nitrogen. There was no interaction between the factors on any of the evaluated variables, except for the weight of quails (P=0,01). The 0.857% digestible methionine + cystine level and the higher inclusion of choline improved egg weight (P=0,03), FC/ egg mass (P=0,02) and egg percentage (P˂0,01). In contrast, there was a reduction in albumen weight (P˂0,01) with increased choline inclusion in the diet. There was a quadratic response on percentage of eggshell, whose optimum level was 0.047% of choline in the diet. The specific gravity of the eggs reduced linearly (P˂0,01), with the inclusion of choline in the diet. Nitrogen excretion showed quadratic inverse response (P=0,04), in which the level of 0.126% of choline, provided reduction of N for the environment in 1.55%, when compared to the treatment without addition of choline. Further research is needed to better define the interaction between methionine + cystine and choline for quails. Thus, it is concluded that for the best egg weight, FC / egg mass, yolk percentage and fecal N reduction in japanese laying quails, the indicated digestible methionine + cystine level is 0.857% and choline is 0.126%.